An intertemporal model of growing awareness - Marie-Louise Vierø (Queen's University, Department of Economics, 2017)
This paper presents an intertemporal model of growing awareness. It provides a framework for analyzing problems with long time horizons in the presence of growing awareness and awareness of unawareness. The framework generalizes both the standard event-tree framework and the framework from Karni and Viero (2017) of awareness of unawareness. Axioms and a representation are provided along with a recursive formulation of intertemporal utility. This allows for tractable and consistent analysis of intertemporal problems with unawareness.
Keywords: D8; D81; D83; D9; 330; Awareness; Unawareness; Intertemporal Utility; Recursive Utility; Reverse Bayesianism